2022
DOI: 10.3389/fmolb.2021.814921
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Aircraft Noise Exposure on Vascular Oxidative Stress, Endothelial Function and Blood Pressure: No Evidence for Adaptation or Tolerance Development

Abstract: Transportation noise is recognized as an important cardiovascular risk factor. Key mechanisms are noise-triggered vascular inflammation and oxidative stress with subsequent endothelial dysfunction. Here, we test for adaptation or tolerance mechanisms in mice in response to chronic noise exposure. C57BL/6J mice were exposed to aircraft noise for 0, 4, 7, 14 and 28d at a mean sound pressure level of 72 dB(A) and peak levels of 85 dB(A). Chronic aircraft noise exposure up to 28d caused persistent endothelial dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…Nitrate-tolerant animals and patients take profit from AT 1 -receptor blockade (Hirai et al, 2003 ; Knorr et al, 2011 ) and angiotensin-converting enzyme (ACE) inhibitor (Berkenboom et al, 1999 ; Heitzer et al, 1998 ; Watanabe et al, 1998 ) therapy. Similar observations were made in noise exposure animal studies, where RAAS activation was prominent as documented by elevated angiotensin-II levels (Munzel et al, 2017a ), additive damage of noise in mice with arterial hypertension by angiotensin-II infusion (Steven et al, 2020 ), and normalization of elevated blood pressure in noise-exposed mice by the ACE inhibitor captopril (Frenis et al, 2021b ). Although the molecular mechanisms of RAAS activation and increased ROS production are likely different in response to chronic nitrate therapy and noise exposure, the downstream health side effects on the cardiovascular system are likely the same (see summarizing scheme in Fig.…”
Section: Clinical Perspective On the Role Of Endothelial Dysfunction ...supporting
confidence: 64%
“…Nitrate-tolerant animals and patients take profit from AT 1 -receptor blockade (Hirai et al, 2003 ; Knorr et al, 2011 ) and angiotensin-converting enzyme (ACE) inhibitor (Berkenboom et al, 1999 ; Heitzer et al, 1998 ; Watanabe et al, 1998 ) therapy. Similar observations were made in noise exposure animal studies, where RAAS activation was prominent as documented by elevated angiotensin-II levels (Munzel et al, 2017a ), additive damage of noise in mice with arterial hypertension by angiotensin-II infusion (Steven et al, 2020 ), and normalization of elevated blood pressure in noise-exposed mice by the ACE inhibitor captopril (Frenis et al, 2021b ). Although the molecular mechanisms of RAAS activation and increased ROS production are likely different in response to chronic nitrate therapy and noise exposure, the downstream health side effects on the cardiovascular system are likely the same (see summarizing scheme in Fig.…”
Section: Clinical Perspective On the Role Of Endothelial Dysfunction ...supporting
confidence: 64%
“…To test whether chronic exposure to aircraft noise results in noise habituation, we exposed animals to noise for up to 28 days, revealing persistent endothelial dysfunction and elevated blood pressure. 114 Additionally, there was a time-dependent increase in the formation of ROS, as observed through dihydroethidium staining and HPLCbased superoxide measurements in the aorta, heart, and brain. The oxidative burst in whole blood peaked after 4 to 7 days of noise exposure.…”
Section: No Tolerance To Cardiovascular Side Effects Of Noisementioning
confidence: 94%
“…The formation of ROS increased gradually with ongoing exposure, indicating that mice did not habituate to chronic noise stress at moderate levels. 114 Noise Preconditioning and MI A significant clinical question concerns whether the side effects of noise are aggravated in susceptible patients, for example, patients with acute coronary syndromes. We addressed this by exposing mice to an average sound pressure level of 72 dB and a peak level of 85 dB for up to 4 days, activating proinflammatory aortic gene expression related to myeloid cell adhesion and diapedesis pathways.…”
Section: Compendium On Environmental Impacts On Cardiovascular Health...mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies in nonhuman primates and rodents showed that chronic noise exposure (4 weeks to 9 months) causes persistent increases in blood pressure, 66,67 which has been linked to impaired vascular reactivity and endothelium-dependent relaxation. 68 Studies in mice have also shown that aircraft noise exposure triggers endothelial dysfunction and vascular inflammation due to oxidative stress, and increased activation and adhesion of leukocytes, [69][70][71] which in turn can promote atherosclerosis. Another key pathway through which noise is thought to impair cardiovascular health is sleep disturbance.…”
Section: Noise and Light Pollutionmentioning
confidence: 99%